Serum Homocystine Level in Women with Severe Preeclampsia (Ibrahim Cardiac Medical Journal, 2017)
Objective: Though preeclampsia (PE) is an age-old disease, its pathology still remains obscure. Available epidemiological evidences suggest that PE is a disease of multiple theories. Recently serum homocystine level is considered as factor to be associated with preecampsia and the higher the level the greater is the severity of preeclampsia. The present study is aimed at investigating this hypothesized association.Methodology: This case-control study was conducted over a period of 24 months from January 2012 to December 2013 in the Department of Obstetrics & Gynaecology, Dhaka Medical College, Dhaka. Pregnant women admitted with severe preeclampsia were the case, while pregnant women attending at the antenatal clinic without preeclampsia were the controls. Severe preeclampsia was diagnosed by blood pressure > 160/110 mm of Hg with proteinuria 3+ or more in dipstick test. The control group comprised of women of 24 - 40 weeks gestation, with blood pressure (both diastolic and systolic) remaining within normal limits without having any medical or obstetric complications. Data were analysed using software SPSS (Statistical Package for Social Sciences) version 16.0. The test statistics used to analyse the data were descriptive statistics, Chi-square (χ2) Test, Student’s t-Test and Receiver-operating characteristic (ROC) curve analysis.Result: Around two-thirds of the patients in both groups were in the age range of 21-30 years with mean age of the cases and control being 25.8 ± 5.2 and 24.1 ± 3.7 years respectively (p = 0.108). Over three-quarters (77.5%) of the patients in case group and 60.0% in control group belonged to middle class (p = 0.091). Majorities of the cases (85.0%) and controls (90.0%) were preterm (gestational age < 37 weeks) with mean gestational age being 33.2 ± 3.3 and 32.3 ± 3.5 weeks in case and control groups respectively (p > 0.05). The patients in either group were predominantly primigravida. Seven (17.5%) patients in the case group gave the history of past preeclampsia as opposed to none in the control group (p = 0.005). Family history of preeclampsia was reported by the case group alone (p = 0.027). Majority (95.0%) of the cases had 3+ proteinuria. Serum homocystine concentration was significantly raised (15.7 ± 8.3 μmol/L) in case group than that in the control group (6.7 ± 1.3 μmol/L) (p < 0.001). Based on the receiver-operator characteristic (ROC) curve, serum homocysteine levels in pregnant women had the best area under the curve (0.975 or 97.5%) with sensitivity and specificity of the predictor variable being 92.5 and 77.5% respectively.Conclusion: The study concluded that homocysteine levels are significantly elevated in patients with preeclampsia compared to the pregnant women without preeclampsia. Homocysteine may be of value in the monitoring of pregnancies to be complicated by preeclampsia.Ibrahim Card Med J 2015; 5 (1&2): 54-60